(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This paper is a collection of short essays written by the American theatre director Anne Bogart and translated into Portuguese by the Brazilian theatre director and researcher Fabiano Lodi. Each one of them is about the impacts of locking down the Theatres and the complete stopping for artistic and cultural activities because of the worldwide Coronavirus pandemic, since 2020 March. Thus, Bogart proposes a review of cultural, political and ethical issues from the historical past to imagine a future in which theatre as an art of encounter will be possible again.